Ação antimicrobiana de análogos da dinoponeratoxina M- PONTXDq3a sobre cepas de Staphylococcus aureus - Silva Júnior, Pedro Nonato da (2024)
The growing incidence of methicillin-resistant Staphylococcus aureus (MRSA) infections is associated with increased mortality rates, generating the interest on the developing of antimicrobial peptides (AMP), such those from the giant ant Dinoponera quadriceps. In order to improve the net positive charge and the antibacterial activity of the AMP, amino acids with positive side chain single substituted analogues have been proposed, mainly arginine or lysine. Thus, the present work aims to study the antimicrobial activity of the analogues of M-PONTX- Dq3a, a 23 amino acid AMP identified in the D. quadriceps venom. M-PONTX-Dq3a[1-15], a fragment containing the 15 central amino acids, and eight derivatives single arginine or lysine substituted analogues were proposed. After, the antimicrobial activity of these peptides was tested against Staphylococcus aureus ATCC 6538P (MSSA) and ATCC 33591 (MRSA) strains. Minimum inhibitory concentration (MIC) and minimum lethal concentration (MLC) were determined, as well the minimum biofilm inhibitory concentration (MBIC). Membrane permeability was assessed using the Crystal violet (CV) assay and flow cytometry using with propidium iodide. The effect of exposure time on microbial viability (Time-Kill) was evaluated. Ultrastructural alterations were evaluated by scanning electron microscopy (SEM). [Arg]3M- PONTX-Dq3a[1-15] and [Arg]4M-PONTX-Dq3a[1-15], both arginine-substituted, showed the lowest MIC and MLC values (both 0.78 μM). In the biofilm formation assays, the peptide [Arg]3M-PONTX-Dq3a [1-15] showed a MBIC of 3.12 μM for the two strains tested. Both peptides were able to change the permeability of the membrane around 80%. The treatment at MIC was able to eliminate bacteria after 2 hours of contact. For treatment with half of the MIC, both strains had a constancy in the number of bacteria up to 12h, which may indicate a bacteriostatic effect. SEM showed that the treatment at the lowest concentration (0.78 μM) of both peptides provided disruption of the cell membrane, destabilized the intercellular interaction and the CLM of [Arg]4M-PONTX-Dq3a [1-15] caused the complete eradication of the bacteria. Thus, this study describes two AMP active against MSSA and MRSA and also are able to inhibit the formation of their biofilms. [Arg]3M-PONTX-Dq3a[1-15] and [Arg]4M- PONTX-Dq3a[1-15] emerge as a new alternative for research substances for the treatment of resistant and/or biofilm-forming strains.